On increasing students’ motivation for studying English as a foreign language at university - Nadezhda G. Pirogova; Grigory A. Rozhkov (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
Most English language teachers support the opinion that the students' learning potential increases, when they are positive about studying a language and are highly motivated. The research into the connection between positive attitude and successful second language acquisition confirms this idea. However, it is important to understand that this correlation is influenced by a variety of factors including complex social and psychological aspects of behaviour. The paper looks at the issues related to attitude to and motivation for learning a foreign language. It describes in detail the implemented project that studied the factors that have an influence on motivation and assessed the impact of using special strategies, materials and assignments on developing a positive attitude to language learning. The project is based on action research, which is a useful method with clear stages that allow a teacher to identify, research and apply teaching strategies as well as to analyze results and make recommendations in order to improve these strategies and educational process as a whole.